FINDING A BALANCE BETWEEN INTELLECTUAL AND SPIRITUAL INTELLIGENCE IN THE MODERN ERA ACCORDING TO IBN KHALDUN - Farghita, Vania Salsabila (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
Abstract: This research aims to understand how to achieve a balance between intellectual and spiritual intelligence in modern times based on Ibn Khaldun's views. The main question asked was how Ibn Khaldun viewed the relationship between intellectual and spiritual intelligence in education. The research method involves an analysis of Ibn Khaldun's major works, especially the book